A Study on GOJEK's Brand Image and Consumer Trust: An Analysis of the Influence of Digital Marketing Strategies and Promotions on GOJEK's Brand Image and Consumer Trust - Setyawan, Muhammad Dimas Arbi; Kanthy, Nur Halizah Wulan Nirmala; Usman , Osly (Manunggal Halim Jaya, 2025)
Digital marketing has become a central pillar in building and strengthening brand image in the contemporary information era. This study provides an in-depth analysis of the influence of digital marketing strategies and promotional activities on GOJEK’s brand image, with consumer trust positioned as a critical mediating variable. A quantitative approach was employed, utilizing Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), implemented through the SmartPLS software. The sample consisted of 100 respondents—users of the GOJEK application in the Mustika Jaya District, Bekasi City—who were selected using purposive sampling. The analysis revealed that digital marketing strategies have a positive and significant effect on both brand image (p = 0.041) and consumer trust (p = 0.027). In contrast, promotional activities have a direct, significant effect on brand image, but also significantly and positively influence consumer trust (p = 0.001). The most notable finding is the significant mediating role of consumer trust in the relationships between digital marketing strategies and brand image (p = 0.050) and between promotion and brand image (p = 0.007). These results underscore that the effectiveness of digital marketing strategies and promotional efforts largely depends on their success in establishing consumer trust initially. The practical implication for companies is the need to prioritize transparency, data security, and two-way interaction as core elements of their digital marketing strategies to enhance brand image fundamentally.